Country Partnership Framework for Georgia for the Period FY19-FY22 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2018)
This Country Partnership Framework (CPF) for FY19–FY22 sets out the World Bank Group’s (WBG) proposals for supporting the Government of Georgia’s vision of developing a market based economy while ensuring nationwide prosperity and strengthening its regional position. Building on the strong foundation put in place by the previous FY14 to FY17 Country Partnership Strategy (CPS), this CPF will work to consolidate gains and move the economy toward addressing next generation development challenges for sustained and inclusive growth and poverty reduction. The CPF proposes a strategic shift in focus from an infrastructure heavy program to one that emphasizes expanding human capital. WBG interventions over the next four years will aim to reduce gaps in human endowments and create economic opportunities that will ensure inclusive and sustainable economic growth. The WBG will support Georgia in sustaining strong productivity led growth while maintaining a direct line of sight to the “Bottom 40” those Georgians whose annual household income falls into the bottom 40 percent of the country. To support the government in achieving the twin goals of eliminating extreme poverty and promoting shared prosperity, the CPF envisages support to Georgia across three focus group areas: (i) enhancing inclusive growth and competitiveness, (ii) investing in human capital, and (iii) building resilience. The CPF will pay special attention to vulnerable groups and lagging regions that have not benefited from the fruits of growth.Interventions will target special groups such as women, youth, and rural communities where most poor people live. Across the three focus areas, the CPF will rely on three engagement principles to guide the selection of interventions: (i) maximizing finance for development (MfD), which aims to leverage the private sector for growth and sustainable development; (ii) spatial equity, as a means to redress currently regional imbalances within the country; and (iii) innovation, given the rapid pace of technological changes and digitization and its effects on productivity and competitiveness. Lending commitments will evolve during the CPF as they have throughout the WBG’s engagement with Georgia and the current portfolio of investments and advisory services and analytics (ASA) will serve as a solid base to enable the WBG to achieve the intended strategic shifts in this CPF.